2011
DOI: 10.1016/j.tiv.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses of Prochilodus lineatus hepatocytes after cylindrospermopsin exposure

Abstract: Cylindrospermopsin is a potent toxicant for eukaryotic cells produced by several cyanobacteria. Recently, primary hepatocyte cultures of Neotropical fish have been established, demonstrating to be a quite efficient in vitro model for cellular toxicology studies. In the current study, a protocol for culture of Prochilodus lineatus hepatocytes was established and utilized to investigate the cellular responses to purified cylindrospermopsin exposure. Hepatocytes were successfully dissociated with dispase, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…Differently than expected and reported for other models (Kinnear, 2010;Lankoff et al, 2007;Liebel et al, 2011) HepG2 cells were not deleteriously affected by CYN exposure at concentrations up to 10-fold the safe limit of 1 lg l À1 as these concentrations were not cytotoxic and, surprisingly, promoted metabolism increase and cell proliferation. These controversy data are then discussed in order to highlight that CYN at low concentrations promote a proliferation of human hepatoma cells (HepG2) and CYP-induction slightly increase CYN toxicity.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Differently than expected and reported for other models (Kinnear, 2010;Lankoff et al, 2007;Liebel et al, 2011) HepG2 cells were not deleteriously affected by CYN exposure at concentrations up to 10-fold the safe limit of 1 lg l À1 as these concentrations were not cytotoxic and, surprisingly, promoted metabolism increase and cell proliferation. These controversy data are then discussed in order to highlight that CYN at low concentrations promote a proliferation of human hepatoma cells (HepG2) and CYP-induction slightly increase CYN toxicity.…”
Section: Discussioncontrasting
confidence: 84%
“…However, values lower than 1 lg l À1 has been suggested by Humpage (2005, 2006). In a previous study a decreases of cell viability and multidrug resistance transporters activity on primary cultured fish hepatocytes exposed to CYN (1-10 lg l À1 ) were described (Liebel et al, 2011). Additionally, the same authors showed an increase of reactive oxygen and nitrogen species concentration related with significant lipid peroxidation in the same cells.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the present study, a similar increase in DNA fragments in comet tails was observed. On the other hand, Liebel et al [37] did not detect any DNA damage in hepatocytes from Prochilodus lineatus exposed to the toxin at concentrations up to 10 µg/ml for 72 h. In that study, however, increased reactive …”
Section: Discussionmentioning
confidence: 67%
“…Hence, accumulation of metals in the fish tissues affects their physiology. Several studies have reported alteration in level of protein, lipid, carbohydrate, and activities of different enzymes in the fish in response to different xenobiotics (Palanisamy et al 2011;Yousafzai and Shakoori 2011;Yacoub and Gad 2012;Liebel et al 2011;Nogueira et al 2011). Since they act as biomarker of the health of fish, their assessment is very important to evaluate the effect of pollution on the fish health.…”
Section: Introductionmentioning
confidence: 99%